1981
DOI: 10.5254/1.3535795
|View full text |Cite
|
Sign up to set email alerts
|

Long Chain Branching in Natural Hevea Rubber-Determination by Gel Permeation Chromatography

Abstract: The hevea brasiltensis rubber contains, besides the insoluble branched entities, linear and branched molecules in the soluble fraction. The branching characteristics found by analyzing fractions of different molecular weight of rubber coagulated from freshly tapped latex, stabilized with hydroxylamine hydrochloride are: (a) molecules with molecular weights above 6.5×104−1.0×105g/mol (depending on the branch points functionality) are branched and molecules below these limits are linear. (b) The relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…One of the most important of the non-hydrocarbon group's presents in NRL is the aldehyde group, which is thought to be responsible for crosslinking between the chains in NRL 27 and their concentration varying from clone to clone 28 . Other compounds, such as lipids, neutral glycolipids and phospholipids, amount to 1.4-3.2%.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important of the non-hydrocarbon group's presents in NRL is the aldehyde group, which is thought to be responsible for crosslinking between the chains in NRL 27 and their concentration varying from clone to clone 28 . Other compounds, such as lipids, neutral glycolipids and phospholipids, amount to 1.4-3.2%.…”
Section: Resultsmentioning
confidence: 99%
“…it is well established that nr is composed of long-chain branched molecules (Campos-López and angulo-sánchez, 1976;angulo-sánchez and Cabaulero-Mata, 1981;Fuller and Fulton, 1990). Fulton and groves showed the presence of long-chain branching and gel in NR by field flow fractionation (FFF): the log r g -log MW conformational plot was shown to have a slope of 0.3 in the high MW range (Fulton and groves, 1997).…”
Section: Chemical Structure Of Nrmentioning
confidence: 99%
“…4,27 Kim et al 5,33 analyzed NR samples with SEC-MALS and showed that the soluble part injected into a SEC system contained very few branched macromolecules, contrary to earlier published studies. [34][35][36] Kim et al 5,33 showed that the soluble part of NR in solution in tetrahydrofuran (THF) was composed of a mixture of linear chains and assumed compact microaggregates (R g % 110-130 nm). They showed that, to more effectively ascertain the mesostructure of NR, a MALS detector needs to be used with SEC to avoid a misunderstanding of the structure, as is the case with most polymers.…”
Section: Introductionmentioning
confidence: 99%